AN ANALYSIS OF ASSOCIATIVE MEANING FROM “ALADDIN” (2019) SOUNDTRACKS LYRICS - Putri, Thalyta Oktariana; Purnamasari, Dewi (Premise: Journal of English Education and Applied Linguistics, 2024)
This paper reviews An Analysis of Associative Meaning From "Aladdin" (2019) Soundtracks Lyrics. This research aims to find meaning in each Aladdin soundtrack as well as the meaning of the lyrics using associative meaning theory. This kind of research is qualitative. The source of this research data is the result of the search for meaning in each existing song, then the result is loaded in the form of tables or data. The result that has been obtained; it can be concluded that the data has associative meaning based on Leech's theory of associative meaning. The results showed that there are 89 data and 4 types of associative meanings found in the 6 soundtracks in the Aladdin movie, 4 of them are; Connotative meaning contains 25 data, Social or Stylistic Meaning contains 24 data, Affective meaning has 23 data, while Collective and Reflective Meaning has 17 data. This study used a qualitative descriptive method in analyzing the data. Leech's theory is used in this study to analyze associative meaning. Implications on Leech's theory are, by observing the collocation of words in lyrics and analysing how these combinations of words form specific associations in the listener's mind. Leech emphasizes the importance of relationships between words in a particular context and how such relationships can form broader meaning, and also by studying lyrics and analysing them by using the Leech Theory framework, readers can develop skills in understanding and analyzing English contextually, not just literally.